El empleo (debido) de la fuerza letal policial en el ordenamiento jurídico español: Una aproximación dogmática - Coca Vila, Ivó (Eguzkilore, 2022)
Can a criminal law system legitimately impose a duty of protection whose compliance may require, in an extreme situation, killing a citizen? This paper aims to answer this question within the framework of the Spanish criminal law system. To this end, I first examine the legitimacy requirements of police duties whose fulfillment requires the use of force. Then, I specifically address the problem of the legitimacy of a duty of protection whose fulfillment requires in the specific case to kill a citizen. Can a criminal law system that claims to be liberal force police officers to shoot a citizen to death? This paper concludes with a final section devoted to condensing the main theses defended in what follows.